Neurologic indications for therapeutic plasma exchange: 2013 update. Issue 4 (31st May 2014) - Gwathmey, Kelly; Balogun, Rasheed A.; Burns, Ted; Balogun, Rasheed A.
<x xml:space="preserve">Abstract</x> Neurologists commonly use therapeutic plasma exchange (TPE) to treat a number of conditions. This concise review considers the most common neurologic indications for TPE. It focuses on Guillain–Barré syndrome and myasthenia gravis and also the role of TPE in chronic inflammatory demyelinating polyneuropathy, Lambert–Eaton syndrome, multiple sclerosis, neuromyelitis optica, paraproteinemic polyneuropathy, Sydenham's chorea, and natalizumab‐associated progressive multifocal leukoencephalopathy. As with any treatment, the proven efficacy, cost, side effects, and availability must be considered before initiation of therapy. J. Clin. Apheresis 29:211–219, 2014. © 2014 Wiley Periodicals, Inc.